Soft skills practiced by managers for employee job performance in Ready Made Garments (RMG) sector of Bangladesh - Sarker, Md Atiqur Rahman; Hashim, Junaidah; Haque, A. K. M. Ahasanul; Mhd. Sarif, Suhaimi; Juhdi, Nurita (Research Publishing Academy, 2019)
Soft skills are essential tools in maintaining employment relations as well as achieving high job performance. The purpose of this study is to explore the contribution of soft skills practiced by manager towards employee job performance specifically at RMG sector in Bangladesh. Data have been collected through two Focus Group Discussions (FGDs) and five in-depth interviews. Thematic analysis yielded four most commonly practiced soft skills in RMG which are communication, leadership, team work and critical thinking. This study reveals that there is a direct positive relationship between soft skills practiced by managers and employees’ job performance. This study has three significant contributions. Firstly, this study is one of the very few studies on soft skills practice set on production based industry from non-western context. Secondly, this study facilitates future comparative studies on service sector as well as on crosscultural perspective. The findings of this study has created further opportunity to conduct study on other production based industries available in Bangladesh and around the globe. Thirdly, the HR practitioners in Bangladesh specifically in production based industry will be more concerned from now about the practice of soft skills.